Vasodilator-Stimulated Phosphoprotein Activity Is Required for Coxiella burnetii Growth in Human Macrophages. - Punsiri M Colonne; Caylin G Winchell; Joseph G Graham; Frances I Onyilagha; Laura J MacDonald; Heike R Doeppler; Peter Storz; Richard C Kurten; Paul A Beare; Robert A Heinzen; Daniel E Voth (PLoS Pathogens)
Coxiella burnetii is an intracellular bacterial pathogen that causes human Q fever, an acute flu-like illness that can progress to chronic endocarditis and liver and bone infections. Humans are typically infected by aerosol-mediated transmission, and C. burnetii initially targets alveolar macrophages wherein the pathogen replicates in a phagolysosome-like niche known as the parasitophorous vacuole (PV). C. burnetii manipulates host cAMP-dependent protein kinase (PKA) signaling to promote PV formation, cell survival, and bacterial replication. In this study, we identified the actin regulatory protein vasodilator-stimulated phosphoprotein (VASP) as a PKA substrate that is increasingly phosphorylated at S157 and S239 during C. burnetii infection. Avirulent and virulent C. burnetii triggered increased levels of phosphorylated VASP in macrophage-like THP-1 cells and primary human alveolar macrophages, and this event required the Cα subunit of PKA. VASP phosphorylation also required bacterial protein synthesis and secretion of effector proteins via a type IV secretion system, indicating the pathogen actively triggers prolonged VASP phosphorylation. Optimal PV formation and intracellular bacterial replication required VASP activity, as siRNA-mediated depletion of VASP reduced PV size and bacterial growth. Interestingly, ectopic expression of a phospho-mimetic VASP (S239E) mutant protein prevented optimal PV formation, whereas VASP (S157E) mutant expression had no effect. VASP (S239E) expression also prevented trafficking of bead-containing phagosomes to the PV, indicating proper VASP activity is critical for heterotypic fusion events that control PV expansion in macrophages. Finally, expression of dominant negative VASP (S157A) in C. burnetii-infected cells impaired PV formation, confirming importance of the protein for proper infection. This study provides the first evidence of VASP manipulation by an intravacuolar bacterial pathogen via activation of PKA in human macrophages.